Experimental determination of scattering processes in the interaction of laser radiation with polyamide 12 powder - Schuffenhauer, Thomas; Stichel, Thomas; Schmidt, Michael (Procedia CIRP, 2020)
Energy density, scanning strategy and laser spot size are some of the parameters influencing the optical energy input during laser-based powder bed fusion of polymers. For newly developed polymer powders, such parameters must still be determined empirically. Understanding the complex mechanisms underlying the beam-matter interaction, including absorption characteristics or multiple scattering behavior, is crucial to predict material processability and to improve interlayer fusion for enhanced final part properties. A measurement system based on two integrating spheres is employed to analyze the scattering processes during the interaction of a CO2 laser beam with polymeric powder materials. The setup is used to measure total reflection from the sample surface as well as unscattered and diffuse transmission through the sample. The resulting optical properties of polyamide 12 powder are evaluated and compared to those of thin films of the same base material. Thus, the influence of particle interfaces on the energy deposition characteristics can be analyzed qualitatively.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Integrating spheres; Laser sintering; Optical properties; Polyamide 12; Polymers; Powder bed fusion